The Role of the Cameraman in Designing the Public Service Advertisement "Titik Pulang" for the Al - Qomariah Islamic Boarding School Foundation - Alfayed, Bergas; Atmaja, Suhendra; Nihayati, Laila (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This work aims to introduce the short film advertisement "Titik Pulang" to the general public, with a focus on raising awareness about the importance of child protection. In addition, this work also aims to build a positive image for the Al-Qomariah Islamic Boarding School Foundation as an institution that cares about education and providing a safe environment for children. Through this advertisement, it is hoped that the public will be educated on the importance of education and child protection as a long-term investment for the nation's progress. Mass communication, especially through the medium of film, plays a strategic role in conveying social messages. *Titik Pulang* delivers a moral message about regret and the importance of making the right decisions in life. In this film project, the author serves as the cameraman. The cameraman plays a crucial role in film production, as they are responsible for capturing video footage according to the director's instructions, who has already designed the script. A cameraman not only needs technical skills to produce high-quality images but also a deep conceptual understanding to select the appropriate camera angles in accordance with the production context. By combining visual and audio elements, this film is designed to evoke emotions and raise awareness of human values. This public service advertisement aims to encourage a change in societal attitudes and behaviors toward social issues, particularly those related to child protection and education. The choice of the main character, Lanang—a motorcycle taxi driver who reflects on the regrets of his past decisions—adds emotional depth to the story, which is expected to inspire viewers to live more wisely. The Al-Qomariah Foundation, as the producer of this project, is committed to making this film an effective tool for public education, hoping to create a positive impact on society and shape the character of future generations.